Arsenic (V) Removal from Aqueous Solution by Produced Iron and Detect Isoterms and Kinetic Adsorption - Roghaye Nourozi; Saeed Azizian (Muhandisī-i Bihdāsht-i Muḥīṭ, 2014)
Background: Zero-valent iron can control the sites contaminated Arsenic (V) used. The aim of this research is Arsenic (V) removal from aqueous solutions using of iron powder and detect isoterms and kinetic adsorption.